Association between Perceived Daylit Area and Self-reported Frequency of Electric Lighting Use in Multi-dwelling Buildings. Issue 1 (2nd January 2022) - Bournas, Iason
ABSTRACT: This paper examines the association between daytime electric lighting use and perceived indoor daylight availability in residential spaces. In addition, occupant preferences were evaluated, in particular which rooms are prioritized in terms of daylight availability. The study deployed a questionnaire survey that was carried out in typical multi-dwelling apartment blocks in Malmö, Sweden (Latitude: 55.6 °N). Occupants were asked to report how often they use electric lighting during daylight hours (EL) in their kitchen, living room and main bedroom, and how much of the floor area they perceive as adequately daylit (DA) throughout the year. Responses EL and DA were measured in seven-point semantic differential scales, and were correlated (Spearman) to evaluate their association for different room groups. Groups were based on age, room function, façade orientation, balcony obstruction and fenestration geometry. In addition, occupants were asked which room they would choose if there had to be one underlit room. Results indicate that EL is strongly associated with DA in the overall room sample (rS = −0.588, p < .01, n = 225). The association is persistent across room groups of different characteristics, with the Spearman rank correlation coefficient ranging between −0.4 and −0.8, and not differing significantly between groups. In terms of preferences, a significantly high proportion of participants would choose the bedroom if there had to be one underlit room (62%, p < .05), while the kitchen was selected by only 5 out of 108 respondents.